2015
DOI: 10.1111/basr.12072
|View full text |Cite
|
Sign up to set email alerts
|

Institutionalization or Decoupling? An Exploratory Analysis of theUNGlobal CompactLEADInitiative

Abstract: Institutionalization occurs when organizations adopt policies and practices in an attempt to increase their legitimacy and competitive position. This process assumes that an organization's formal policies (macro-level) are translated into organizational practices (micro-level). This translation, however, can fail to occur, resulting in organizational decoupling and de-institutionalization. Drawing on an institutionalization typology based on different levels of legitimacy (macro) and taken-for-grantedness (mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Differences can be made by agents of change through symbiotic relationships with the structures and processes of the organization. Junaid, Leung, and Buono [19] (p. 492) explain that perceived legitimacy is important for organizations for competitive success and refers to "coercive isomorphism" being the social and political pressure to conform to perceived legitimacy. Masocha and Fatoki [20] find that coercive isomorphism, through policies, laws, standards, and regulations, is a significant driver of small businesses adopting, for example, initiatives related to sustainability.…”
Section: Talloires Application and Theorymentioning
confidence: 99%
“…Differences can be made by agents of change through symbiotic relationships with the structures and processes of the organization. Junaid, Leung, and Buono [19] (p. 492) explain that perceived legitimacy is important for organizations for competitive success and refers to "coercive isomorphism" being the social and political pressure to conform to perceived legitimacy. Masocha and Fatoki [20] find that coercive isomorphism, through policies, laws, standards, and regulations, is a significant driver of small businesses adopting, for example, initiatives related to sustainability.…”
Section: Talloires Application and Theorymentioning
confidence: 99%
“…Third, this study contributes to the emerging literature on the UNGC/SDGs (e.g. Berliner and Prakash, 2015;Hamann et al, 2009;Junaid et al, 2015;Rasche et al, 2013) by showing the lack of accountability in the adoption of UN principles by organizations. Although sustainability reporting has been critiqued for its opacity and lack of transparency by many studies (Boiral, 2013;Cho et al, 2012;Hahn and Lülfs, 2014;Talbot and Boiral, 2018), few scholars have focused specifically on UNGC principles and the SDGs (for recent exceptions, see Rosati and Faria, 2019;Van der Waal and Thijssens, 2020).…”
Section: Theoretical Contributionsmentioning
confidence: 77%
“…In fact, it may be present in communication on all principles of the UNGC and SDGs. Bluewashing practices have been highlighted by several scholars (Berliner and Prakash, 2015;Hamann et al, 2009;Junaid et al, 2015;Rasche et al, 2013), although only a few empirical studies have analyzed such tendencies. For instance, Van der Waal and Thijssens (2020) analyzed the disclosures of the 2000 largest stock-listed corporations worldwide and concluded that involvement in SDGs seems to be primarily motivated by the search for legitimacy.…”
Section: Improving Legitimacy Through Sustainability Reporting and Un...mentioning
confidence: 99%
See 1 more Smart Citation